Abandoned Housing Projects In Malaysia: Risk Management Capabilities During Rehabilitation - Abdul Aziz, Abdullah; Hamzah, Abdul-Rahman; Ali Mohammed, Alashwal (2016)
Rehabilitation is a key-initiative undertaken to overcome a prevailing problem in Malaysia that is the abandonment of housing projects during construction. However, rehabilitation is a complex process and involves various parties. The purpose of this paper is to identify critical risks during the rehabilitation process and to evaluate capabilities of main stakeholders in managing these risks. To achieve this objective, a questionnaire survey was used and targeted three groups, namely authorities, builders, and liquidators. The data were analyzed using Relative Importance Index (RII) and Chi-square to determine top ranking risks and risk categories. The results showed 18 risk variables and indicated Managerial Risk as the top risk category. The results also showed feeble risk management capabilities of the three groups. The findings of this paper attempt to fill a significant gap in the literature pertaining to this subject. The identification of the risks and capabilities pitfalls is expected to provide invaluable information to facilitate the rehabilitation process to complete the abandoned projects successfully.